Contralateral suppression of otoacoustic emissions: Input-Output functions in neonates - Campos, Ualace de Paula; Hatzopoulos, Stavros; Kochanek, Krzysztof; Sliwa, Lech; Skarzynski, Henryk; Carvallo, Renata Mota Mamede (Medical science monitor, 2011)
The literature suggests that contralateral acoustic stimulation (CAS) alters the amplitude of the distortion product otoacoustic emissions (DPOAEs), but it is still unknown whether the DPOAE Input/Output (I/O) functions are also affected. To elucidate this aspect of the DPOAEs, the present study assessed the effects of CAS on DPOAE I/O functions at the frequencies of 2 kHz and 4 kHz, in a sample of term neonatal subjects. Sixty randomly selected neonates were included in the study. The DPOAE I/O functions were obtained at 2 kHz and 4 kHz, in the presence of a 60 dB SPL broad band-contralateral white noise, using the TDH39 headphones contralaterally. DPOAEs were recorded up to a stimulus level of L2 = 35 dB peSPL. Significant DPOAE amplitude suppression effects were observed at various L2 stimulus levels for both tested frequencies at 2 and 4 kHz. In contrast, the corresponding DPOAE slopes showed various alterations that were not statistically significant. The data from the present study show that contralateral acoustic stimulation significantly affects only the amplitude of the DPOAE I/O functions; the slope is affected, but not significantly. This observation can shed light on the nature of CAS, suggesting that the latter is primarily a linear phenomenon without the cochlear compression and non-linear components seen in the healthy cochlea. From the available data it is not possible to infer whether the sample size has influenced the obtained results and the study should be repeated with a larger sample size and assessing more frequencies.